Pengembangan Media Pembelajaran Papan Perkalian Untuk Meningkatkan Hasil Belajar Peserta Didik Kelas II MI Al-Azhar Menganti Gresik - Lidya Septiani; Ria Resti Fauziah; M. Heri Prianto (El-Miaz: Jurnal Pemikiran dan Pendidikan Dasar, 2025)
Learning outcomes are an achievement achieved by students in the ability to master a number of learning materials. In mathematics learning, especially multiplication material, students should understand the concept of multiplication in order to get maximum learning results. However, research conducted at MI Al-Azhar shows that in mathematics learning multiplication material, not all students understand the concept of multiplication because there is no use of learning media using concrete objects. This study aims to describe the process of developing multiplication board learning media using concrete objects, testing the practicality of learning media, and testing the effectiveness of learning media. This multiplication board learning media was developed to improve the learning outcomes of grade II students at MI Al-Azhar Menganti Gresik. Researchers used the RnD research type with the ADDIE model using observation research instruments, student response questionnaires, and pretest and posttest understanding tests on students. The results of the development of this multiplication board media in the feasibility test had an average percentage score of 96.8%, meaning that this board learning media is very good or very suitable for use. Then the results of the practicality test got a percentage of 98% from the results of the implementation of learning and 96.2% from the student response questionnaire. which means this media is practical to use. In addition, it can also improve students' conceptual understanding with evidence of the n gain test from the pretest and posttest understanding tests which have an average score of 0.79 which means students experienced an increase after using the multiplication board learning media.